(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2021)
The study was carried out to observe growth, production and profit of prawn, stripped mullet (Mugil cephalus) and corsula mullet (Rhinomugil corsula) at different stocking ratio under polyculture in the Bagerhat district for four months. The experiment was designed as a randomized block design and had three treatments based on stocking ratio with three replicates in each treatment. Juveniles of prawn (Macrobrachium rosenbergii) and fingerlings of fin fishes (stripped mullet and corsula mullet) were stocked at a stocking ratio of 3:1:1, 4:1:1 and 5:1:1/m2 in T1, T2 and T3, respectively. Prawn and fin fishes were fed with a commercial diet and farm made formulated feed on a daily basis. Recorded water quality parameters were within suitable ranges of prawn and fish culture. Higher growth (43.0 g) of the prawn was achieved in T1 followed by T2 (41.0 g) and T3 (38.0 g), but prawn growth was not significantly different between T1 and T2. The growth and survival rate of prawn, stripped mullet and corsula mullet were lower in T3, where the stocking ratio was higher. Higher production of the prawn was obtained in T2 (1148.0 kg/ha) than those of T1 (954.6 kg/ha) and T3 (1083.0 kg/ha). But significantly (p<0.05), higher production of stripped mullet was found in T1 (650.0 kg/ha) and T2 (579.5 kg/ha) than T3 (500.5 kg/ha). Similarly, higher production of corsula mullet was found in T1 (850.0 kg/ha) and T2 (834.9 kg/ha) than T3 (719.8 kg/ha). However, combined production and net profit of prawn and fin fish farming were significantly (p<0.05) higher in T2 (2562.4 kg/ha, BDT 277,384.51/ha) followed by T3 (2303.3 kg/ha, BDT 229,693.95/ha) and T1 (2454.6 kg/ha, BDT 179,393.31/ha). So from a production and economic point of view, polyculture of prawn and fin fish at a stocking ratio of 4:1:1/m2 is more profitable compared to other stocking ratios and this system may be suggested to disseminate at coastal farmers’ level. J. Asiat. Soc. Bangladesh, Sci. 47(1): 67-78, June 2021